The Effect of Content Marketing and Brand Awareness on Purchase Decisions on Naabakehouse - Wardhani, Nadya Puspita; Fitriyah, Zumrotul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of content marketing and brand awareness on consumer purchasing decisions at Naabakehouse SMEs in Surabaya. This research uses a quantitative approach with data collected through questionnaires from 95 respondents who have seen the content and purchased Naabakehouse products. The data analysis technique used is Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). The results show that content marketing and brand awareness have a positive and significant effect on consumer purchasing decisions. These findings highlight the importance of content strategy and brand awareness in shaping consumer behavior in the digital era.